Egypt spectral shift control concept for OECD VVER-1000 leu assembly computational benchmark using Monte-Carlo code serpent; Научная инициатива иностранных студентов и аспирантов; Т. 2 - Elzayat T. (Science as a vocation and career, 2021)
Заглавие с титульного экрана